2020
DOI: 10.4178/epih.e2020030
|View full text |Cite
|
Sign up to set email alerts
|

Medication errors among Iranian emergency nurses: A systematic review

Abstract: studies conducted among emergency ward nurses in Iran. The studies were restricted to full-text, peer-reviewed studies published from inception to December 2019, in the Persian and English languages, that evaluated MEs among emergency ward nurses in Iran. RESULTS: Eight studies met the inclusion criteria. Most of the nurses (58.9%) had committed MEs only once. The overall mean rate of MEs was 46.2%, and errors made during drug administration accounted for 41.7% of MEs. The most common type of administration er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Also, the unpredictability and complex nature of emergency departments (EDs), the critical condition of most patients, lack of teamwork, and large volumes of work due to the inadequacy of the patient and nurse ratios convert the emergency department to a high-risk area for patient adverse events [ 2 ]. The prevalence of adverse events in ED is higher and varied from 4 to 68% [ 3 ]. According to a study by Kakemam et al, the prevalence of adverse events in Iran is between 7 and 40% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the unpredictability and complex nature of emergency departments (EDs), the critical condition of most patients, lack of teamwork, and large volumes of work due to the inadequacy of the patient and nurse ratios convert the emergency department to a high-risk area for patient adverse events [ 2 ]. The prevalence of adverse events in ED is higher and varied from 4 to 68% [ 3 ]. According to a study by Kakemam et al, the prevalence of adverse events in Iran is between 7 and 40% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, a study conducted by Di Simone et al (2018) showed that the main causes of medication errors in emergency rooms are fatigue due to work overload, inadequate knowledge of medications and lack of specific guidelines on medication administration safety, which is consistent with the findings of the present study. However, a study conducted by Hosseini Marznaki et al (2020) found that the incidence rate of medication errors made by the ED nurses in Iran was high (46.2%). This study reported that extended shifts and inadequate knowledge of drugs were the main causes of these errors, which agrees with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies that were analyzed, the improvement in healthcare after the use of CPOE is meaningful, since errors of administration were recorded before and after its application, and a reduction was observed [63,[69][70][71]. The reduction in the incidence of drug administration errors and the reduction in time to administration is of paramount importance in the pandemic situation because of the shortage in resources in critical care settings, and it must not be overlooked [79,80]. Although this situation does not directly affect the tasks usually performed by physicians or nursing professionals, it is considered one of the most limiting factors in providing the necessary care on time, so any tool capable of alleviating burdens should be considered potentially useful [78].…”
Section: Discussionmentioning
confidence: 99%